2022
DOI: 10.2147/orr.s382232
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Outcomes of Reduction Surgery for Degenerative Lumbar Spondylolisthesis Using Long Arm Pedicle Screws

Abstract: Objective Until now, the spondylolisthesis reduction technique has relied on posterior instrumentation using long arm pedicle screws. In this way, the segments will be brought into alignment with the other vertebrae with the pedicle mats being tightened. The aim of this study is to acknowledge whether reduction surgery for degenerative lumbar spondylolisthesis (DLS) using long arm pedicle screws is able to correct the listhesis and spinopelvic parameters. Methods We car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…The Oswestry Disability Index (ODI) showed a decrease from 60% to 25%, reflecting a marked improvement in disability due to back pain. This reduction is in line with the results from similar surgical interventions, where significant decreases in ODI scores were commonly observed in the study of Sim DS et al, [16] Another study of Cheng X et al, [17] observed significant improvements in the leg pain VAS and ZCQ score for both cohorts at 3 months and 2 years after surgery. Radiological outcomes of the current study also showed significant improvements.…”
Section: Discussionsupporting
confidence: 87%
“…The Oswestry Disability Index (ODI) showed a decrease from 60% to 25%, reflecting a marked improvement in disability due to back pain. This reduction is in line with the results from similar surgical interventions, where significant decreases in ODI scores were commonly observed in the study of Sim DS et al, [16] Another study of Cheng X et al, [17] observed significant improvements in the leg pain VAS and ZCQ score for both cohorts at 3 months and 2 years after surgery. Radiological outcomes of the current study also showed significant improvements.…”
Section: Discussionsupporting
confidence: 87%